2012
DOI: 10.7317/pk.2012.36.4.470
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Various Amine Groups onto Poly(glycidyl methacrylate)-g-MWNTs and their Application as Biosensor Supports

Abstract: A tyrosinase-immobilized biosensor was developed based on various amine-modified multi-walled carbon nanotube (MWNT) supports for the detection of phenolic compounds. MWNTs with various amine groups were prepared by radiation-induced graft polymerization of glycidyl methacrylate (GMA) onto MWNT supports and the subsequent amination of poly(GMA) graft chains. The physical and chemical properties of the poly(GMA)-grafted MWNT supports and the aminated MWNT supports were investigated by SEM, XPS, and TGA. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…2+ complex onto the TEDA-modified MWNT electrode [10]. The results of this report show that the grafted poly(GMA) chain can act as a polymer binder and the unpaired electron of the immobilized Figure 1: Preparation overview of the ECL-GCE and ECL-SPE based on vinyl polymer-g-MWNT.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…2+ complex onto the TEDA-modified MWNT electrode [10]. The results of this report show that the grafted poly(GMA) chain can act as a polymer binder and the unpaired electron of the immobilized Figure 1: Preparation overview of the ECL-GCE and ECL-SPE based on vinyl polymer-g-MWNT.…”
Section: Introductionmentioning
confidence: 84%
“…ADPA was synthesized in accordance with a previous paper [10]. In detail, diphosphoric acid (0.562 mol) was dried under reduced pressure for 12 hrs and then dissolved in tetrahydrofuran (THF, 210 mL).…”
Section: Synthesis Of Acryloyl Diphosphoric Acid (Adpa)mentioning
confidence: 99%
“…With the polymerization of GMA, the epoxy groups in poly-GMA can be modified to alcohol [ 50 ], amine [ 51 ], phosphonic acid, sulfonic acid [ 52 ], and so forth. [ 53 , 54 ]. The epoxy group of poly-GMA can be generated onto a CNT surface by radiation-induced polymerization.…”
Section: Radiolytic Functionalization Of Cntsmentioning
confidence: 99%
“…The physical and chemical properties of the GMA-grafted MWNT and aminated MWNT have been investigated using IR, SEM, XPS, and TGA. However, Chung et al [ 54 ] reported that the increased diameter of the MWNTs indicated the successful attachment of epoxy groups by the radiation-induced graft polymerization of GMA. Amines can be covalently introduced onto MWNT supports with epoxy groups through an SN 2 reaction.…”
Section: Radiolytic Functionalization Of Cntsmentioning
confidence: 99%
“…5,6 예를 들어 폴리우레아, 폴리프로필렌, 폴리아크릴산 등 의 고분자를 CNT의 표면에 도입시키면 CNT의 손상이 적고 고분자 매질에 효과적으로 분산시킬 수 있는 것으로 보고되 고 있다. 7,8 한편, 폴리(페닐렌 설파이드)(PPS)는 필름과 섬유뿐만 아니 라 자동차 부품, 기계 부품, 전기•전자 등 다양한 전자제품 및 산업용 분야에 사용되는 고성능 엔지니어링 플라스틱이 다.…”
Section: 서 론unclassified